Negative electrode sheet, electrochemical device and electronic device of sodium ion battery

By depositing sodium metal on the negative electrode sheet of the sodium ion battery and forming a carbon material coating, the problem of low energy density of sodium ion battery is solved, cycling performance and safety are improved, and higher energy density is achieved.

CN114709368BActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202210391946.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-26
Publication Date
2025-04-18
Estimated Expiration
2041-06-26

AI Technical Summary

Technical Problem

Due to the low capacity and voltage platform of positive and negative electrode materials, sodium ion batteries have a large gap in energy density compared with lithium ion batteries, and cannot be commercially available.

Method used

Using a negative electrode sheet without negative electrode active material, by depositing sodium metal on the surface of the negative electrode current collector and forming a carbon material coating on its surface, the overpotential of sodium metal deposition is reduced and the formation of sodium dendrites is inhibited.

Benefits of technology

It effectively improves the cycling performance of sodium ion batteries, enhances the kinetic performance of sodium metal nucleation, reduces the risk of self-discharge of the battery, improves safety, and improves energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114709368B_ABST
    Figure CN114709368B_ABST
Patent Text Reader

Abstract

The present application provides a negative electrode plate, an electrochemical device and an electronic device of a sodium ion battery, wherein the negative electrode plate includes a negative electrode current collector, a carbon material coating formed on at least a portion of the surface of the negative electrode current collector, and a sodium metal layer formed on at least a portion of the surface of the carbon material coating away from the negative electrode current collector, the thickness of the carbon material coating is less than or equal to 10 μm, the carbon material coating includes a carbon material and a polymer binder, the carbon material includes an oxygen-containing group, and the mass content of oxygen atoms in the carbon material is ≥ 0.1%. The negative electrode plate of the sodium ion battery provided by the present application deposits metallic sodium on the surface of the negative electrode current collector during the first charge, and the metallic sodium formed by the deposition can adhere to the carbon material coating on the surface of the negative electrode current collector, and the carbon material coating can effectively reduce the overpotential of sodium metal deposition, inhibit the formation of sodium dendrites, and is conducive to improving the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the invention application with application number 202110742798.7, application date June 26, 2021, and invention name “Negative electrode sheet, electrochemical device and electronic device for sodium ion battery”. Technical Field

[0002] The present application relates to the field of energy storage technology, and in particular to a negative electrode sheet, an electrochemical device and an electronic device of a sodium ion battery. Background Art

[0003] As energy and environmental issues become increasingly prominent, the new energy industry has received more and more attention. Lithium-ion batteries have been widely used as an important new energy storage device in recent years due to their high energy density and good cycle performance. However, due to the scarcity of active material resources related to lithium-ion batteries, battery costs have always remained high, and at the same time, they are facing severe problems such as the depletion of related resources. Therefore, it is necessary to develop other low-cost metal ion secondary battery systems.

[0004] Sodium-ion batteries have become a hot research direction in recent years due to their low cost, abundant resources, and similar manufacturing processes to lithium-ion batteries. However, due to the low gram capacity and voltage platform of the current positive and negative electrode materials of sodium-ion batteries, the energy density of sodium-ion batteries is still far behind that of lithium-ion batteries, and they cannot be truly commercialized. In the context of the energy density of positive electrode materials being unable to be broken through, directly using sodium metal (theoretical specific capacity 1166mAh / g) as the negative electrode has become an effective method to significantly increase the energy density of the battery. However, sodium-ion batteries are difficult to commercialize due to the poor chemical stability of sodium metal in the air, its low melting point (98°C), and the fact that sodium metal is prone to dendrites during the electrochemical cycle. Summary of the invention

[0005] In view of this, the present application proposes a negative electrode plate, an electrochemical device and an electronic device for a sodium ion battery, which can effectively inhibit the formation of dendrites of sodium metal during the electrochemical cycle and improve the cycle performance of the battery.

[0006] In a first aspect, the present application provides a negative electrode plate for a sodium ion battery, the negative electrode plate comprising a negative electrode current collector and a carbon material coating formed on at least a portion of the surface of the negative electrode current collector, the thickness of the carbon material coating being less than or equal to 10 μm, and the carbon material coating comprising a carbon material and a polymer binder.

[0007] In combination with the first aspect, in a feasible implementation manner, the negative electrode plate satisfies at least one of the following conditions:

[0008] (1) The carbon material includes at least one of mesophase carbon microspheres, graphite, natural graphite, expanded graphite, artificial graphite, glassy carbon, carbon-carbon composite materials, carbon fiber, hard carbon, porous carbon, highly oriented graphite, three-dimensional graphite, carbon black, carbon nanotubes and graphene;

[0009] (2) The mass proportion of the carbon material in the carbon material coating is 90% to 99%;

[0010] (3) The mass proportion of the carbon material in the carbon material coating is 94% to 97%;

[0011] (4) The thickness of the carbon material coating is 0.3 μm to 10 μm;

[0012] (5) The thickness of the carbon material coating layer is 1 μm to 7 μm.

[0013] In combination with the first aspect, in a feasible implementation manner, the negative electrode plate satisfies at least one of the following conditions:

[0014] (6) The negative electrode current collector comprises at least one of a metal foil, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, a carbon paper current collector and a composite current collector;

[0015] (7) The negative electrode current collector has a porous structure, and the negative electrode current collector includes at least one of a porous aluminum foil, a porous copper foil, and a porous stainless steel foil.

[0016] In combination with the first aspect, in a feasible implementation manner, the negative electrode plate further includes a sodium metal layer formed on at least a portion of the surface of the carbon material coating away from the negative electrode current collector.

[0017] In combination with the first aspect, in a feasible implementation manner, the mass content of the sodium metal layer in the negative electrode plate is 0.1% to 1%.

[0018] In combination with the first aspect, in a feasible implementation manner, the negative electrode plate satisfies at least one of the following conditions:

[0019] (8) The carbon material includes an oxygen-containing group, wherein the oxygen-containing group is selected from at least one of a carboxyl group, a hydroxyl group and an ether group;

[0020] (9) The carbon material includes oxygen-containing groups, and the mass content of oxygen atoms in the carbon material is ≥ 0.1%.

[0021] In combination with the first aspect, in a feasible embodiment, the polymer binder includes at least one of sodium cellulose, sodium carboxymethyl cellulose, hydroxypropyl cellulose, sodium hydroxymethyl cellulose, potassium hydroxymethyl cellulose, diacetyl cellulose, polyacrylic acid, sodium alginate, styrene-butadiene rubber, acrylic butadiene rubber, polypyrrole, polyaniline, epoxy resin and guardo gum.

[0022] In a second aspect, the present application provides an electrochemical device, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that the negative electrode sheet is the negative electrode sheet described in the first aspect above.

[0023] In combination with the second aspect, in a feasible embodiment, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer formed on at least a portion of the surface of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a sodium transition metal oxide, a polyanionic compound and a Prussian blue compound.

[0024] In a third aspect, the present application provides an electronic device, wherein the electronic device comprises the electrochemical device according to the second aspect.

[0025] Compared with the prior art, this application has at least the following beneficial effects:

[0026] The present application provides a negative electrode sheet, an electrochemical device, and an electronic device for a sodium ion battery, wherein the negative electrode current collector surface of the negative electrode sheet has no negative electrode active material, and during the first charge, metallic sodium is deposited on the surface of the negative electrode current collector, so that the metallic sodium formed by the deposition can adhere to the carbon material coating on the surface of the negative electrode current collector, and the carbon material coating can effectively reduce the overpotential of sodium metal deposition, inhibit the formation of sodium dendrites, and help improve the cycle performance of the battery. During the discharge process, metallic sodium can be converted into sodium ions and return to the positive electrode to achieve cyclic charge and discharge. And the carbon material coating can improve the kinetics of sodium metal nucleation in sodium ion batteries. Since metallic sodium is generated in the subsequent cycle process, the sodium ion battery does not have a voltage before the first charge, so the sodium ion battery can be stored for a long time without self-discharge, and even if the battery is short-circuited, it will not generate current, and has extremely high safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A schematic diagram of the structure of the negative electrode plate of the sodium ion battery provided in an embodiment of the present application. DETAILED DESCRIPTION

[0028] The following is a preferred implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also considered to be within the scope of protection of the embodiment of the present invention.

[0029] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0030] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number itself, and “multiple” in “one or more” means more than two.

[0031] The above-mentioned summary of the invention of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0032] First aspect

[0033] The present application provides a negative electrode sheet of a sodium ion battery, such as Figure 1 As shown, the negative electrode plate 1 includes a negative electrode current collector 11 and a carbon material coating 12 formed on at least a portion of the surface of the negative electrode current collector 11, the thickness of the carbon material coating 12 is less than or equal to 10 μm, and the carbon material coating 12 includes a carbon material and a polymer binder.

[0034] In the above scheme, the thickness of the carbon material coating on the surface of the negative electrode current collector is relatively small and cannot play the role of the negative electrode active material. The negative electrode plate of the present application is a negative electrode plate without negative electrode active material. During the first charge, metallic sodium is deposited on the surface of the negative electrode current collector so that the deposited metallic sodium can adhere to the carbon material coating on the surface of the negative electrode current collector. The carbon material coating can effectively reduce the overpotential of sodium metal deposition and inhibit the formation of sodium dendrites, which is beneficial to improving the cycle performance of the battery. During the discharge process, metallic sodium can be converted into sodium ions and return to the positive electrode to achieve cyclic charge and discharge.

[0035] Carbon material coating can improve the kinetics of sodium metal nucleation in sodium ion batteries. Since metallic sodium is produced in the subsequent cycle process, sodium ion batteries do not have voltage before the first charge, so sodium ion batteries can be stored for a long time without self-discharge, and even if the battery is short-circuited, no current will be generated, which has extremely high safety. Since there is no negative active material on the surface of the negative current collector and only the negative current collector is used, the battery can obtain a higher energy density than the metallic sodium negative electrode.

[0036] As an optional technical solution of the present application, the negative electrode current collector 11 includes at least one of a metal foil, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, a carbon paper current collector and a composite current collector. More specifically, the metal foil can be copper foil, aluminum foil, stainless steel foil, iron foil, zinc foil, titanium foil, etc., the metal foam current collector can be copper foam, aluminum foam, zinc foam, etc., and the metal mesh current collector can be copper mesh, aluminum mesh, etc. The negative electrode current collector 11 can also be a composite current collector formed by a metal foil and a metal foam, or a composite current collector formed by a metal foil and a metal mesh, or a composite current collector formed by a metal foil and a polymer base film, which is not limited here.

[0037] Since sodium ions do not form alloys with aluminum, based on the considerations of cost reduction and weight reduction, aluminum-based current collectors are preferably used, including any one of aluminum foil, aluminum alloy foil and aluminum-based composite current collector. The aluminum-based composite current collector includes a polymer base film and aluminum foil and / or aluminum alloy foil formed on both sides of the polymer base film. Specifically, the aluminum-based composite current collector is a "sandwich" structure, with the polymer base film located in the middle, and aluminum foils are provided on both sides thereof, or aluminum alloy foils are provided on both sides thereof. It can also be that aluminum foil is provided on one side of the polymer base film and aluminum alloy foil is provided on the other side. The polymer base film is any one of polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, poly(p-phenylene terephthalamide), polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, and polycarbonate. Preferably, the aluminum-based composite current collector selected in the present invention has better ductility, which is beneficial to maintaining the integrity of the electrode during the sodium deposition / stripping process.

[0038] Optionally, the thickness of the negative electrode current collector 11 is 3 μm to 15 μm, specifically 3 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm or 15 μm, etc., and of course, it can also be other values ​​within the above range, which are not limited here. If the negative electrode current collector is too thick, the energy density of the battery will decrease, and if the negative electrode current collector is too thin, the processing performance of the battery will decrease.

[0039] As an optional technical solution of the present application, the negative electrode current collector 11 has a porous structure, and the negative electrode current collector includes at least one of a porous aluminum foil, a porous copper foil, and a porous stainless steel foil. The negative electrode current collector has a porous structure, which can increase the specific surface area of ​​the negative electrode current collector, and the increase can alleviate the volume change of the negative electrode sheet and inhibit the formation of dendrites.

[0040] As an optional technical solution of the present application, the thickness of the carbon material coating 12 is 0.3μm to 10μm; specifically, it can be 0.3μm, 0.5μm, 1.0μm, 1.4μm, 1.8μm, 2.2μm, 3.5μm, 4.0μm, 4.5μm, 4.9μm, 5.5μm, 6.0μm, 7.0μm, 8.0μm, 9.2μm or 10μm, etc. Of course, it can also be other values ​​within the above range, which are not limited here. When the carbon material coating on the surface of the negative electrode current collector 11 is too thick, the battery energy density decreases and the negative electrode-free effect cannot be achieved; when the carbon material coating on the surface of the negative electrode current collector 11 is too thin, it will cause too few sodium metal nucleation sites, and the sodium embedding overpotential cannot be effectively improved, causing sodium dendrites to easily grow toward the isolation membrane, deteriorating the battery cycle performance. Preferably, the thickness of the carbon material coating is 1 μm to 7 μm; more preferably, the thickness of the carbon material coating is 3 μm to 5 μm.

[0041] As an optional technical solution of the present application, the carbon material coating 12 includes a carbon material and a polymer binder. Wherein, the carbon material includes at least one of mesophase carbon microspheres, graphite, natural graphite, expanded graphite, artificial graphite, glassy carbon, carbon-carbon composite materials, carbon fibers, hard carbon, porous carbon, highly oriented graphite, three-dimensional graphite, carbon black, carbon nanotubes and graphene. It can be understood that by forming a carbon material coating on the surface of the negative electrode current collector, the conductivity of sodium ion diffusion can be increased, the sodium insertion overpotential can be reduced, and the formation and growth of sodium dendrites can be inhibited.

[0042] Preferably, the carbon material includes at least two of mesophase carbon microspheres, graphite, natural graphite, expanded graphite, artificial graphite, glassy carbon, carbon-carbon composites, carbon fibers, hard carbon, porous carbon, highly oriented graphite, three-dimensional graphite, carbon black, carbon nanotubes and graphene. In one embodiment, the carbon material can be a mixture of carbon black, graphene and carbon nanotubes in a mass ratio of 1:1:1. It can be understood that, relative to the use of a single carbon material, the mixed use of two or more carbon materials can expand the conductivity of the carbon material and improve the conductivity of the carbon material.

[0043] As an optional technical solution of the present application, the mass proportion of the carbon material in the carbon material coating 12 is 90% to 99%; specifically, it can be 90%, 90.5%, 91%, 91.3%, 92.8%, 94%, 94.8%, 95%, 95.6%, 96.2%, 96.5%, 97%, 98% or 99%, etc., of course, it can also be other values ​​within the above range, which are not limited here. If the mass proportion of carbon material in the coating is too much, that is, the mass proportion of polymer binder is too small, the adhesion of the carbon material coating will decrease, and problems such as coating peeling and cracking will easily occur during processing. If the mass proportion of carbon material in the carbon material coating is too small, the conductivity of the carbon material coating will decrease, and the sodium embedding overpotential cannot be effectively improved. Sodium dendrites are easily formed, and the battery cycle performance is reduced. Preferably, the mass proportion of the carbon material in the carbon material coating 12 is 94% to 97%.

[0044] As an optional technical solution of the present application, the carbon material includes an oxygen-containing group, and the oxygen-containing group can be selected from at least one of a carboxyl group, a hydroxyl group and an ether group. After the sodium ion battery is charged for the first time, sodium metal is deposited on the surface of the carbon material coating away from the negative electrode current collector. Since the carbon material includes an oxygen-containing group, the oxygen-containing group has good sodium affinity and is easy to preferentially combine with sodium ions to form a uniform sodium metal core, thereby reducing the overpotential of subsequent sodium insertion reactions, improving the uniformity of sodium metal deposition, inhibiting the formation and growth of sodium dendrites, and improving the cycle performance of the sodium metal negative electrode.

[0045] As an optional technical solution of the present application, the mass content of oxygen atoms in the carbon material is ≥ 0.1%, and the mass content of oxygen atoms can specifically be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc., and of course it can also be other values ​​within the above range, which is not limited here. Too little oxygen atom content in the carbon material is not conducive to the formation of uniform sodium metal nuclei by sodium ions, and is not conducive to improving the uniformity of sodium metal deposition.

[0046] Furthermore, if Figure 1 As shown, the negative electrode plate 1 further includes a sodium metal layer 13 formed on at least a portion of the surface of the carbon material coating 12 away from the negative electrode current collector 11. Since the sodium metal barrier is low, the sodium insertion overpotential of the carbon material coating 12 can be reduced, and the overpotential of the entire negative electrode plate can be reduced. The sodium metal layer 13 can completely cover the surface of the carbon material coating 12, or can partially cover the surface of the carbon material coating 12.

[0047] As an optional technical solution of the present application, the mass content of the sodium metal layer 13 in the negative electrode plate 1 is 0.1% to 1%, specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or 1%, etc. Of course, it can also be other values ​​within the above range, which are not limited here. If the mass content of the sodium metal layer in the negative electrode plate is too high, too much sodium metal will easily react with air and water, causing processing difficulties and dendrite growth. If the mass content of the sodium metal layer in the negative electrode plate is too low, too little sodium metal will be combined with the carbon material, and the sodium metal cannot be effectively used to reduce the sodium embedding overpotential and reduce the overpotential of the entire negative electrode plate.

[0048] As an optional technical solution of the present application, the polymer binder in the carbon material coating 12 includes at least one of sodium cellulose, sodium carboxymethyl cellulose, hydroxypropyl cellulose, sodium hydroxymethyl cellulose, potassium hydroxymethyl cellulose, diacetyl cellulose, polyacrylic acid, sodium alginate, styrene-butadiene rubber, acrylic butadiene rubber, polypyrrole, polyaniline, epoxy resin and guardo gum. The polymer binder has high viscosity and mechanical strength, which can ensure the integrity of the contact interface between the carbon material coating and the negative electrode current collector, inhibit dendrite growth, and improve cycle performance.

[0049] As an optional technical solution of the present application, the method for preparing the negative electrode sheet comprises the following steps:

[0050] The carbon material is placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1 and stirred for 1 to 6 hours, and the reaction time is controlled to control the oxygen content;

[0051] The reacted carbon material was washed with deionized water, filtered, placed in an oven, and dried at 80°C;

[0052] The dried carbon material and polymer binder are added to a solvent and stirred into a uniform slurry, the slurry is coated on a negative electrode current collector (specifically, copper or aluminum foil), and dried to obtain a pole piece; wherein the solvent can be selected from at least one of water, acetone, N-methylpyrrolidone, dimethylformamide, and ethanol;

[0053] The electrode is placed in a physical vapor deposition device, and a uniform sodium metal layer is formed on the surface of the electrode by ion sputtering to obtain a negative electrode.

[0054] Second aspect

[0055] The present application provides an electrochemical device, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet of the first aspect.

[0056] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer formed on at least a portion of the surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material may include at least one of a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.

[0057] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, 0 <x≤1。

[0058] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO4) n- valence state.

[0059] Polyanionic compounds can also be those with sodium ions, transition metal ions, tetrahedral (YO4) n- A class of compounds containing anion units and halogen anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; the halogen may be at least one of F, Cl and Br.

[0060] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S and Si, and n represents (YO4) n- valence state; Z represents a transition metal, which may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl and Br.

[0061] Polyanionic compounds include NaFePO4, Na3V2(PO4)3, NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1).

[0062] The Prussian blue compound may be a compound having sodium ions, transition metal ions and cyanide ions (CN-). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The Prussian blue compound may be, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0 <a≤2,0<b<1,0<c<1。

[0063] As an optional technical solution of the present application, the positive electrode active material layer may further include a conductive agent to improve the conductivity of the positive electrode. The present application does not specifically limit the type of the conductive agent, and it may be selected according to actual needs. As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers.

[0064] As an optional technical solution of the present application, the positive electrode active material layer may further include a binder to firmly bond the positive electrode active material and the optional conductive agent to the positive electrode current collector. The present application does not specifically limit the type of binder, and it can be selected according to actual needs. As an example, the binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA) and carboxymethyl chitosan (CMCS).

[0065] As an optional technical solution of the present application, the positive electrode current collector can be a conductive carbon sheet, a metal foil, a carbon-coated metal foil, a porous metal plate or a composite current collector, wherein the conductive carbon material of the conductive carbon sheet can be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene and carbon nanofibers, and the metal material of the metal foil, the carbon-coated metal foil and the porous metal plate can be independently selected from at least one of copper, aluminum, nickel and stainless steel. The composite current collector can be a composite current collector formed by a metal foil and a polymer base film.

[0066] The positive electrode current collector 11 is, for example, one or more of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh and carbon-coated aluminum foil, preferably aluminum foil.

[0067] The positive electrode sheet can be prepared according to conventional methods in the art. Usually, the positive electrode active material and optional conductive agent and binder are dispersed in a solvent (such as N-methylpyrrolidone, referred to as NMP) to form a uniform positive electrode slurry, which is then coated on the positive electrode current collector, and then dried and cold pressed to obtain the positive electrode sheet.

[0068] The isolation membrane in the sodium ion battery of the present application can be any material suitable for an isolation membrane of an electrochemical energy storage device in the art, for example, it can be at least one of, but not limited to, polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber.

[0069] The electrolyte may include an organic solvent and an electrolyte sodium salt. As an example, the organic solvent may be one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, fluoroethylene carbonate, ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and methyl tert-butyl ether; the electrolyte sodium salt may be one or more of sodium hexafluorophosphate, sodium bis(trifluoromethanesulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, and sodium chloride.

[0070] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, to obtain a battery cell, or the battery cell can be obtained after winding; the battery cell is placed in a packaging shell (which can be a soft package, a square aluminum shell, a square steel shell, a cylindrical aluminum shell and a cylindrical steel shell), the electrolyte is injected and sealed to obtain a sodium ion battery.

[0071] Example

[0072] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0073] 1) Preparation of positive electrode

[0074] Fully dissolve 10wt% polyvinylidene fluoride binder in N-methylpyrrolidone, add 10wt% carbon black conductive agent and 80wt% Na4Fe3(PO4)2(P2O7) positive electrode active material to make a uniformly dispersed positive electrode slurry. Evenly apply the positive electrode slurry on the surface of aluminum foil, and then transfer it to a vacuum drying oven for full drying. Roll the obtained pole piece, and then punch it out to obtain the target disc.

[0075] 2) Preparation of negative electrode sheet

[0076] Adding carbon material and sodium alginate into water and stirring to form a uniform slurry, coating the slurry on the negative electrode current collector, drying and cutting to obtain a negative electrode sheet without a negative electrode structure;

[0077] The negative electrode plate is placed in a physical vapor deposition device, and a sodium metal layer is formed on the surface of the negative electrode plate by ion sputtering to obtain a negative electrode plate.

[0078] 3) The isolation membrane is made of polyethylene (PE) porous polymer film.

[0079] 4) Preparation of electrolyte

[0080] Ethylene glycol dimethyl ether (DME) is used as an organic solvent, and then fully dried sodium salt NaPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0081] 5) Preparation of button cells

[0082] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and the electrolyte is added to assemble into a button battery.

[0083] According to the above preparation method, negative electrode examples 1 to 24 and comparative examples 1 to 10 were prepared, and their specific parameters are shown in Table 1.

[0084] Table 1

[0085]

[0086]

[0087]

[0088] Here, “ / ” indicates that the content of the substance is 0.

[0089] Performance Test:

[0090] Performance parameter test of negative electrode

[0091] 1) Thickness of carbon material coating:

[0092] The cross-sectional imaging of the electrode pieces cut by liquid nitrogen quenching was performed by SEM, and the thickness of the carbon material coating was measured by secondary electron imaging.

[0093] 2) Battery performance test

[0094] At 25°C, the battery prepared in the example was charged to 50 μA at a rate of 0.1C, and the most negative potential obtained during the process was recorded as the overpotential;

[0095] At 25°C, the batteries prepared in the examples and comparative examples were charged to 4V at a rate of 0.1C and discharged to 1V at a rate of 0.1C, and full charge and discharge cycle tests were performed until the capacity of the sodium ion battery was less than 80% of the initial capacity. The first-cycle discharge specific capacity and the number of cycles were recorded. The specific data are shown in Table 2.

[0096] Table 2

[0097]

[0098]

[0099] According to the test results of Examples 1 to 6 and Comparative Examples 1 and 2, when the thickness of the carbon material coating on the surface of the negative electrode current collector is in the range of 0.3 μm to 10 μm, the first-cycle discharge specific capacity of the battery is high, the battery has a high energy density, and the carbon material coating can improve the sodium insertion overpotential, inhibit the formation of sodium dendrites, and improve the cycle performance of the battery. According to the test results of Comparative Example 1, if the thickness of the carbon material coating is too thick, the battery energy density decreases, and the effect of improving the battery energy density of the sodium ion battery without a negative electrode structure cannot be achieved. According to the test results of Comparative Example 2, if the thickness of the carbon material coating is too thin, there will be too few sodium metal nucleation sites, and the sodium insertion overpotential will be difficult to improve, causing sodium dendrites to easily grow toward the isolation membrane, and the battery cycle performance will decrease. Preferably, the thickness of the carbon material coating is 1 μm to 7 μm.

[0100] According to the test results of Examples 7 to 11 and Comparative Examples 3 and 4, when the mass proportion of carbon material in the carbon material coating is 90% to 99%, it can effectively improve the sodium insertion overpotential, inhibit the growth of sodium dendrites, and the battery cycle performance can meet the use requirements. According to the test results of Comparative Example 3, the mass proportion of carbon material in the carbon material coating is too small, the conductivity of the carbon material coating decreases, the first-cycle discharge specific capacity of the battery decreases, the improvement of the sodium insertion overpotential is not obvious, and the battery cycle performance decreases. According to the test results of Comparative Example 4, the mass proportion of carbon material in the carbon material coating is too large, the adhesion of the carbon material coating decreases, and the coating is prone to peeling, cracking and other problems during processing, and the battery cycle performance decreases. Preferably, the mass proportion of carbon material in the carbon material coating is 94% to 97%.

[0101] According to the test results of Example 3 and Examples 12 to 14, compared with the use of a single carbon material, the mixed use of two or more carbon materials can expand the conductivity dimension of the carbon material, improve the conductivity of the carbon material, and improve the first-cycle discharge capacity of the battery.

[0102] According to the test results of Example 3 and Examples 15 to 17, Comparative Examples 5 and 6, when the carbon material includes oxygen-containing groups, the oxygen-containing groups have good sodium affinity and are easy to preferentially combine with sodium ions to form uniform sodium metal cores, reduce the overpotential of subsequent sodium insertion reactions, improve the uniformity of sodium metal deposition, inhibit the formation and growth of sodium dendrites, and improve the cycle performance of the sodium metal negative electrode. The oxygen content of the carbon material in Comparative Example 6 is too low, and the effect of improving sodium metal nucleation is small. The overpotential of its sodium insertion reaction is reduced compared to Comparative Example 5 (the carbon material does not contain oxygen), but it is not as obvious as the overpotential reduction in Example 3 and Examples 15 to 17.

[0103] According to the test results of Examples 3 and 18, the negative electrode current collector of Example 18 has a porous structure, which can increase the specific surface area of ​​the negative electrode current collector. The increase can alleviate the volume change of the negative electrode plate, inhibit dendrite formation, and improve the cycle performance of the battery.

[0104] According to the test results of Examples 19 to 24 and Comparative Examples 7 and 9, it can be known that when the mass content of the sodium metal layer in the negative electrode plate is in the range of 0.1% to 1%, the sodium insertion overpotential can be effectively reduced. In Comparative Example 7, no sodium metal layer is formed on the surface of the carbon material coating, and the overpotential of the carbon material coating is relatively increased, which is not conducive to improving the electrochemical performance of the battery. The mass content of the sodium metal layer in the negative electrode plate in Comparative Example 8 is too low, which will result in too little sodium metal combined with the carbon material, and the sodium metal cannot be effectively utilized to reduce the sodium insertion overpotential and reduce the overpotential of the entire negative electrode plate. The mass content of the sodium metal layer in the negative electrode plate in Comparative Example 9 is too high, and too much sodium metal is easy to react with air and water, causing processing difficulties, resulting in dendrite growth, and reduced battery cycle performance.

[0105] According to the test results of Examples 1 to 24 and Comparative Example 10, it can be seen that Comparative Example 10 only uses the negative electrode current collector as the negative electrode, and does not form a carbon material coating to reduce the overpotential of sodium insertion. The overpotential of the battery is the highest and the cycle performance is the worst. It can be seen that by forming a carbon material coating on the surface of the negative electrode current collector, the overpotential of the battery can be effectively reduced and the cycle performance of the battery can be improved.

[0106] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

Claims

1. An electrochemical device, which is a sodium ion battery without negative electrode active material, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The negative electrode plate includes a negative electrode collector, a carbon material coating formed on at least a portion of the surface of the negative electrode collector, and a sodium metal layer formed on at least a portion of the surface of the carbon material coating away from the negative electrode collector, the mass content of the sodium metal layer in the negative electrode plate is 0.1% to 0.7%, the thickness of the carbon material coating is 1 μm to 10 μm, the carbon material coating includes a carbon material and a polymer binder, the carbon material includes oxygen-containing groups, and the mass content of oxygen atoms in the carbon material is 0.1% to 1%.

2. The electrochemical device according to claim 1, characterized in that It satisfies at least one of the following conditions: (1) The carbon material includes at least one of mesophase carbon microspheres, natural graphite, expanded graphite, artificial graphite, glassy carbon, carbon-carbon composite materials, carbon fibers, hard carbon, porous carbon, highly oriented graphite, three-dimensional graphite, carbon black, carbon nanotubes and graphene; (2) The mass proportion of the carbon material in the carbon material coating is 90% to 99%; (3) The mass proportion of the carbon material in the carbon material coating is 90% to 97%; (4) The mass proportion of the carbon material in the carbon material coating is 94% to 97%; (5) The thickness of the carbon material coating is 1 μm to 5 μm; (6) The thickness of the carbon material coating is 3 μm to 5 μm.

3. The electrochemical device according to claim 1, characterized in that It satisfies at least one of the following conditions: (7) The negative electrode current collector comprises at least one of a metal foil, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, a carbon paper current collector and a composite current collector; (8) The negative electrode current collector has a porous structure, and the negative electrode current collector includes at least one of a porous aluminum foil, a porous copper foil, and a porous stainless steel foil.

4. The electrochemical device according to claim 3, characterized in that The negative electrode current collector is an aluminum-based current collector, and the aluminum-based current collector includes any one of aluminum foil, aluminum alloy foil and aluminum-based composite current collector.

5. The electrochemical device according to claim 1, characterized in that The thickness of the negative electrode current collector is 3 μm to 15 μm.

6. The electrochemical device according to claim 1, characterized in that The mass content of the sodium metal layer in the negative electrode plate is 0.1% to 0.5%.

7. The electrochemical device according to claim 1, characterized in that The oxygen-containing group is selected from at least one of a carboxyl group, a hydroxyl group and an ether group.

8. The electrochemical device according to claim 1, characterized in that The polymer binder includes at least one of sodium cellulose, sodium carboxymethyl cellulose, hydroxypropyl cellulose, sodium hydroxymethyl cellulose, potassium hydroxymethyl cellulose, diacetyl cellulose, polyacrylic acid, sodium alginate, styrene-butadiene rubber, acrylic butadiene rubber, polypyrrole, polyaniline, epoxy resin and guardo gum.

9. The electrochemical device according to claim 1, characterized in that The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer formed on at least a portion of the surface of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of a sodium transition metal oxide, a polyanionic compound and a Prussian blue compound.

10. An electronic device, characterized in that: The electronic device comprises the electrochemical device according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-performance negative electrode for sodium ion battery and preparation method thereof

    CN108336301A

  • Sodium-philic conductive carbon nanotube framework material, and preparation method and application thereof

    CN110577208A

  • Positive pole piece and sodium-ion battery

    CN111799470A

  • Sodium metal negative electrode deposition substrate and preparation method and application thereof

    CN112133902A

Cited By

  • Sodium-philic ultrathin aluminum current collector, preparation method thereof and application of sodium-philic ultrathin aluminum current collector in negative-electrode-free sodium ion battery

    CN120649022A